A Systematic Review of the Efficacy and Safety of Desipramine for Treating ADHD - Ghanizadeh, Ahmad (Current Drug Safety, 2013)
This review article systematically and critically summarizes the current evidence regarding desipramine for treating children and adolescents with attention deficit hyperactivity disorder (ADHD). PRISMA guideline was used for gathering the data. The databases of PubMed/Medline and Google scholar were electronically searched. This review included controlled clinical trials investigating the efficacy of desipramine for treating children and adolescents with ADHD. The primary outcome measure was clinical improvement measured by valid and reliable objective instruments in order to assess the severity of ADHD clinical symptoms. Adverse effects were evaluated as well. Out of 267 titles under the study, thirty three articles mentioned desipramine for treating ADHD. Two trials met the inclusion criteria. Desipramine decreases ADHD clinical symptoms. However, there are many concerns about its safety and efficacy. In view of serious concerns about its safety and lack of enough well-controlled trials providing strong evidence about the efficacy of desipraimine, it should be prescribed for treating children with ADHD with a high precaution, and further well-controlled trials should be performed.
Keywords: children